Nonlinearity parameter B/A of the low-salinity seawater - KOZACZKA, E.; GRELOWSKA, G. (Archives of Acoustics, 1994)
The theoretically and experimentally determined values of the nonlinearity parameter B/A, reported in the literature, were obtained predominantly for high-salinity seawater. This work contains the experimental and theoretical investigation results of nonlinearity for low-salinity seawater, especially for the Baltic Sea. The theoretical method represents a thermodynamic approach. It is based on the variation of the sound velocity with changes in pressure, temperature and salinity. Annual changes of the nonlinearity parameter B/A in the South Baltic are determined by means of this method. The experimental method was based on the distortion of the finite amplitude sine wave emitted by a piston acoustic source. The growth of the second harmonic component is measured using a circular receiver which is coaxial with the source. In order to determine the B/A parameter, the experimental measurements were compared to the theoretical results which incorporated the nonlinear parameter. Measurements were carried out in several points of the South Baltic. The investigation results agree well in most cases. To achieve satisfactory accuracy, it is necessary to take into account the effects of both the diffraction and attenuation on the second harmonic amplitude by interpretating the measurement results.